Preliminary research on influence of welding parameters strength at welded joints in ribbed reinforcing steel - Bilić, Željko; Samardžić, Ivan; Mišina, Nedjeljko; Stoić, Katarina (2020)
As already known, no proper control or process control parameter which absolutely guarantees a high level quality of joints made by electro-resistive welding has been established so far, especially when all possible parameters are taken into account during the welding process. Due to the process of butt-welding being very short-lived, ensuring quality of the joints is a difficult and under-researched problem. The application of non-destructive testing methods to the control interface joints is also not reliable. Therefore, further research in this area should concentrate on studying the influence of basic welding parameters, and calculating their direct or indirect impact can serve to achieve a highquality welded joint with for practice sufficient accuracy.
Bibliografija: 6 jed.
Abstract.
Keywords: Zavarivanje -- Čelik -- Vlačna čvrstoća